ONE ASEAN ONE RESPONSE ROADSHOW: COMPARATIVE ANALYSIS OF DISASTER COMMUNICATION FOR REGIONAL PREPAREDNESS AND RESPONSE MECHANISM IN THE PHILIPPINES AND MALAYSIA - Nugraha, Ilham; Krismansyah, Windra; Hidayat, Muhammad (Ridwan Institute, 2024)
The ASEAN Coordinating Centre for Humanitarian Assistance on disaster management (AHA Centre) is a multilateral, regional, and multistakeholder, multilateral organization with a focus on regional disaster preparedness and response coordination. This study aims to explore whether the AHA Centre successfully disseminated information about the ASEAN disaster management mechanism through the One ASEAN One Response Roadshow in the Philippines and Malaysia, while examining how intercultural communication differences in these two countries influenced the success of the information dissemination process. A case study approach will be utilized to provide a detailed examination of the phenomenon within real-life contexts, considering multiple perspectives and collecting abundant qualitative data. The findings from group discussions and observations indicate that participation of each representatives from government and UN agencies, international and intergovenrmental organisations, non-governmental organsiation, private sectors and media fulfilling the disaster communication foundation as an effective process of dissemination and information exchange. The results from this study reinforce the significance of a well-structured communication framework in enhancing disaster preparation and response, providing valuable insights for future disaster management initiatives within ASEAN region and beyond. Lastly, after understanding roles and responsibility of each organisation, the FGD was conducted to test appropriateness of employing information exchange from different cultures, contextualise key common understanding for an effective sharing experience, and expedite the inward and outward looking for each organisation to adjust and implement better approach for adaptability purpose.